A radioligand receptor binding assay for measuring of insulin secreted by MIN6 cells after stimulation with glucose, arginine, ornithine, dopamine, and serotonin - Asai, Seiya; Žáková, Lenka; Selicharová, Irena; Marek, Aleš; Jiráček, Jiří (Analytical and bioanalytical chemistry, 2021)
We adapted a radioligand receptor binding assay for measuring insulin levels in unknown samples. The assay enables rapid and accurate determination of insulin concentrations in experimental samples, such as from insulin-secreting cells. The principle of the method is based on the binding competition of insulin in a measured sample with a radiolabeled insulin for insulin receptor (IR) in IM-9 cells. Both key components, radiolabeled insulin and IM-9 cells, are commercially available. The IR binding assay was used to determine unknown amounts of insulin secreted by MIN6 β cell line after stimulation with glucose, arginine, ornithine, dopamine, and serotonin. The experimental data obtained by the IR binding assay were compared to the results determined by RIA kits and both methods showed a very good agreement of results. We observed the stimulation of glucose-induced insulin secretion from MIN6 cells by arginine, weaker stimulation by ornithine, but inhibitory effects of dopamine. Serotonin effects were either stimulatory or inhibitory, depending on the concentration of serotonin used. The results will require further investigation. The study also clearly revealed advantages of the IR binding assay that allows the measuring of a higher throughput of measured samples, with a broader range of concentrations than in the case of RIA kits. The IR binding assay can provide an alternative to standard RIA and ELISA assays for the determination of insulin levels in experimental samples and can be especially useful in scientific laboratories studying insulin production and secretion by β cells and searching for new modulators of insulin secretion.
Keywords: Insulin; radioligandová zkouška; Glucose; Cell Line; Radioligand; Rats, Wistar; inzulin; Insulin receptor; Binding assay; serotonin; Radioligand Assay; Insulin secretion; glukosa; radioimunoanalýza; potkani Wistar; Arginine; dopamin; β Cells; Langerhansovy ostrůvky; krysa rodu Rattus; Dopamine; ornithin; Animals; sekrece inzulinu; lidé; Radioimmunoassay; Humans; zvířata; Ornithine; beta-buňky; Rats; myši; buněčné linie; arginin; Insulin-Secreting Cells; Islets of Langerhans; Mice; Serotonin; Insulin Secretion; Secretagogue